Pengaruh Musik Mozart terhadap Tingkat Kecemasan Pasien Dokter Gigi - Abdillah, Nova; Saleh, Edwyn (Universitas Muhammadiyah Yogyakarta, 2010)
The aim of this study was to examine the influence of Mozart’s music as an instrument in reducing patient’s anxiety while visiting dentist’s clinic. 100 subjects between age of 13 - 70 years and fulfilled the inclusion criteria participated in this study. In this quasi-experimental study the subjects were questioned about their feeling of anxious before entered and after went out from the dentist’s practice room, while Mozart’s music playing during the treatment. Patient’s anxiety score were obtained by Modified Dental Anxiety Scale (MDAS). Data were evaluated using Wilcoxon Signed Rank Test. This study showed that there ’s changes ofpatient ’s anxiety level after listening Mozart’s music during dental treatment. One patient experienced increasing of dental anxiety levels, 48patients didn ’t experience of dental anxiety level changes, and 51 patients experienced decreasing of dental anxiety levels. Result of statistical test showed p=0,000 (p0,5) it means that there ’s a significant differences ofpatient’s anxiety levels after dental treatment with Mozart ’s music playing in dentist ’s practice room. In conclusion, Mozart ’s music can be used as an alternative instrument to reduce anxiety levels of the patient during dental treatment at the dentist’s clinic.Penelitian ini bertujuan untuk mengetahui pengaruh musik Mozart terhadap tingkat kecemasan pasien yang berkunjung ke klinik dokter gigi. Penelitian ini dilakukan dengan metode kuasi-eksperimental pada 100 pasien yang berusia 13 - 70 tahun dan memenuhi kriteria inklusi subjek penelitian. Pada subjek penelitian dilakukan penilaian terhadap kecemasan sebelum masuk dan sesudah keluar dari ruang praktek dokter gigi, dimana pada saat perawatan berlangsung, diputarkan musik Mozart. Skor kecemasan dinilai dengan Modified Dental Anxiety Scale (MDAS). Data yang diperoleh dianalisis dengan uji Wilcoxon Signed Rank Test. Hasil penelitian ini menunjukkan adanya perubahan tingkat kecemasan sesudah dilakukan perawatan dengan mendengarkan musik Mozart. Satu pasien mengalami peningkatan tingkat kecemasan, 48 pasien tidak mengalami perubahan tingkat kecemasan, dan 51 pasien mengalami penurunan tingkat kecemasan. Hasil uji statistis menunjukkan hasil p=0,000 (p0,05) yang artinya terdapat perbedaan yang sangat bermakna pada perubahan tingkat kecemasan pasien sesudah diputarkan musik Mozart.Hasil penelitian ini dapat disimpulkan bahwa musik Mozart dapat digunakan sebagai alternatif piranti untuk mengurangi kecemasan pasien yang sedang melakukan perawatan kesehatan gigi di klinik dokter gigi.